UPAYA PENINGKATAN PENGETAHUAN IBU MENYUSUI TENTANG PENGGUNAAN PUDING DAUN KELOR (MORINGA OLEIFERA) SEBAGAI PELANCAR ASI - SURYATIM PRATIWI, YOPI; Sri Handayani, Sri Handayani; Yesvi Zulfiana (LP4M STIKes Karsa Husada Garut, 2023)
The Infant Mortality Rate (IMR) in Indonesia is still high. The infant mortality rate is largely caused by nutritional factors. Exclusive breastfeeding can reduce infant morbidity and mortality. The most common reason found in breastfeeding mothers who stop breastfeeding is due to insufficient breast milk production. The use of plants/vegetables that function as galactogogues can be used as an alternative to increase breast milk production. Moringa leaves are one of the plants that people often use to increase breast milk production. Based on this, it is necessary to provide education to increase knowledge about the use of Moringa oleifera leaf pudding as a breast milk enhancer. The aim of the education is to increase postpartum mothers' knowledge about the use of Moringa leaf pudding as a breast milk enhancer. This health education activity was carried out on August 7 2023 in Jempong Baru Village, Sekarbela District, Mataram City. The method used in this service activity uses the lecture method, and the media uses power points and leaflets. Posttest results showed that postpartum mothers experienced an increase in knowledge after being given health education about the use of Moringa leaf pudding as a breast milk enhancer. After the service activities, postpartum mothers are expected to be able to develop processed keor leaves into pudding as an effort to increase the flow of breast milk.